Mathematical transition: evaluating students’ academic progress and adaptation from primary to secondary education - Ismayanti, Syifa; Pujiati, Amelia (Al-Mufid, 2025)
The transition from primary to secondary education represents a critical phase in students’ mathematical development, often marked by cognitive, curricular, and emotional challenges. This study aimed to examine students’ academic progress in mathematics during their first semester of lower secondary education in Majalengka, Indonesia, and to analyze how structured instruction and curricular coherence influence their learning outcomes. A quantitative pre-test–post-test design was employed involving 38 seventh-grade students at SMP Negeri 2 Majalengka. Data were collected using a standardized mathematics achievement test aligned with the Kurikulum Merdeka competencies, covering five mathematical domains: number, measurement, geometry, algebra, and data. Descriptive and inferential analyses were conducted using SPSS version 26. The results revealed a significant improvement in students’ mathematics achievement (t(37) = 9.284, p < 0.001), with a large effect size (Cohen’s d = 1.51), indicating substantial educational impact. The greatest gains were observed in algebra and geometry, reflecting the development of abstract reasoning and problem-solving skills. These findings support the Curriculum Alignment Theory, demonstrating that vertically coherent mathematics instruction promotes continuity in learning, and align with the Cognitive-Affective Adaptation Theory, which emphasizes the importance of emotional engagement and self-efficacy during academic transitions. The results underscore the critical role of instructional alignment, affective support, and contextualized pedagogy in facilitating successful mathematical transition. This study contributes empirical evidence from the Indonesian context, highlighting that structured and coherent mathematics instruction not only enhances students’ cognitive performance but also fosters positive attitudes and adaptive motivation during the transition to secondary education. The implications are discussed for curriculum design, teacher professional development, and policy interventions aimed at improving educational continuity in mathematics.